State-of-the-Art Data Acquisition Equipment and Field Measurement Techniques for Conveyor Belts - David J. Kruse (Society for Mining, Metallurgy & Exploration, 2004)
Accurate field measurements are essential when validating a conveyor design. They are fundamental in determining a conveyor's behavior, its long-term maintenance requirements, and the life expectancy/ condition of the installed equipment. Field measurements are also invaluable in forensic engineering, particularly when vital equipment has failed This paper will discuss a wide variety of data acquisition equipment, field measurement techniques and accuracies achieved State-of-the-art, custom designed monitoring equipment, as well as, ''08-the-shely instruments and sensors, will be discussed.